Impact of COVID-19 pandemic restrictions and relaxation on pediatric respiratory virus hospitalizations in Southwest China: a retrospective study - Gong, Ting; He, Fengqi; Zhao, Yongle; Lu, Shuya; Tian, Daiyin (Frontiers in Virology, 2025)
BackgroundResearch from multiple regions indicates that Coronavirus disease of 2019 (COVID-19) pandemic has altered the epidemiological characteristics of respiratory viruses.MethodsThis single-center retrospective study included children hospitalized for lower respiratory tract infections (LRTIs) from 2017 to mid-2024. Data on respiratory syncytial virus (RSV), adenovirus (ADV), influenza A virus (IAV), influenza B virus (IBV), and parainfluenza virus (PIV)—were collected and analyzed across pre-pandemic, pandemic, and post-pandemic periods.ResultsA total of 59173 children were included. Detection rates were 34.97% (8553/24459) pre-pandemic, 21.93% (4621/21067) during the pandemic, and 21.64% (2953/13647) post-pandemic. Mixed infections rates significantly decreased during the pandemic (0.78%) and post-pandemic (0.78%) compared to pre-pandemic levels (1.63%) (P < 0.001). RSV was the most prevalent virus across all periods (P < 0.001). Following non-pharmaceutical interventions (NPIs) in 2020, detection rates declined significantly. After restrictions eased in 2021, RSV, PIV, and IBV surged, while IAV continued to decline until its resurgence in spring 2023 (P < 0.001). Certain viruses showed altered seasonal patterns: during the spring and summer of 2021, RSV detection rates exceeded those of previous years, while the expected winter 2022 peak was delayed by approximately six months. IAV peaks disappeared during winters of 2020 and 2021, peaking in spring 2023. IBV peaked in autumn 2021 and winter 2023. PIV had an unusual rise in summer 2020, peaking in autumn, delayed by about five months. The peak in the first half of 2024 returned to its normal timing. ADV appeared to be unaffected, with increased detection in 2022, and decreased in 2023 and 2024.ConclusionEpidemiological patterns of respiratory viruses have been altered by multiple influencing factors. The significance of vaccination, hygiene practices, public health interventions and etc. was emphasized in addressing pandemics. Additionally, ongoing dynamic monitoring is essential due to the evolving epidemiology.